2021
DOI: 10.3390/biomedicines9101429
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus and Cancer: Epidemiology, Physiopathology and Prevention

Abstract: Individuals with type 2 diabetes mellitus are at greater risk of developing cancer and of dying from it. Both diseases are age-related, contributing to the impact of population aging on the long-term sustainability of health care systems in European Union countries. The purpose of this narrative review was to describe, from epidemiological, pathophysiological and preventive perspectives, the links between type 2 diabetes mellitus and the most prevalent cancers in these patients. Multiple metabolic abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 109 publications
(138 reference statements)
0
13
0
2
Order By: Relevance
“…As discussed above, inflammatory exacerbation due to increased cytokines levels has been recognized as one of the main keys to poor prognosis in COVID-19. The anti-inflammatory properties of metformin are already known, suggesting a beneficial effect for COVID-19 disease [ 52 ]. Despite this, immunomodulatory actions of metformin in the context of COVID-19 remain unclear.…”
Section: How Antidiabetic Treatment Influences Sars-cov-2 Infectionmentioning
confidence: 99%
“…As discussed above, inflammatory exacerbation due to increased cytokines levels has been recognized as one of the main keys to poor prognosis in COVID-19. The anti-inflammatory properties of metformin are already known, suggesting a beneficial effect for COVID-19 disease [ 52 ]. Despite this, immunomodulatory actions of metformin in the context of COVID-19 remain unclear.…”
Section: How Antidiabetic Treatment Influences Sars-cov-2 Infectionmentioning
confidence: 99%
“…After adjustment the hazard ratio was 0.63 (95% CI 0.53, 0.75) [ 78 ]. An overview of studies with metformin performed in the last 5 years showed a possible protective effect in the incidence of colorectal, hepatic, head and neck and lung cancers [ 79 ].…”
Section: Cancermentioning
confidence: 99%
“…4 This connection is likely independent of shared risk factors between diabetes and colorectal cancer. 5 Instead, the association between diabetes and colorectal cancer may depend on other mechanisms such as alterations to the gut microbiome, increased inflammation in the gut, hyperinsulinemia in early stage type 2 diabetes and activation of cancer promoting pathways. 6 Colorectal cancer is a heterogeneous disease, displaying considerable differences in molecular markers, which correlate with anatomical tumor location and other clinical and patient characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with diabetes mellitus, especially those with type 2 diabetes, have an increased risk of developing colorectal cancer 4 . This connection is likely independent of shared risk factors between diabetes and colorectal cancer 5 . Instead, the association between diabetes and colorectal cancer may depend on other mechanisms such as alterations to the gut microbiome, increased inflammation in the gut, hyperinsulinemia in early stage type 2 diabetes and activation of cancer promoting pathways 6 …”
Section: Introductionmentioning
confidence: 99%